MATHEMATICAL LITERACY IN ALGEBRA REASONING - Syawahid, Muhammad (International Journal of Insights for Mathematics Teaching (IJOIMT), 2019)
This study aims to describe prospective mathematics teacher?s mathematical literacy in algebra reasoning and thinking process in solving mathematical literacy problems. This study used a qualitative case study approach by choosing two prospective mathematics teacher who solved problems with algebraic reasoning. The result has shown that prospective mathematics teacher has algebraic reasoning in type functional thinking and use generalization in solving mathematical literacy problems. Functional thinking reasoning type used table representation and number manipulation to find and compare the value of charge in justification and decision making, while use generalization reasoning type used supposition, algebra expression, conditioning, and number manipulation to find and compare the value of charge in justification and decision making. Furthermore, use generalization reasoning type interpreted thrice in conditioning before general interpreted.